REPRESENTASI BUDAYA BUGIS-MAKASSAR DALAM FILM UANG PANAI = MAHA(L)R (Analisis Semiotika Roland Barthes) - Kaputra, Nur Ilfath; Rimayanti, Nita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Bugis tribe is an ethnic group that has long lived in the area of South Sulawesi. The area where the Bugis tribe resides in the central part of South Sulawesi makes this tribe in direct contact with other tribes residing in the province. For Bugis society, marriage means taking each other or Bugisnya siala '. One of the marriage customs in this Bugis Tribe is Money Panai ', where this tradition of the groom brings a certain amount of money to the prospective bride who will be used for the purpose of holding weddings and other wedding expenses. As for one film that raised the value of traditional / original culture is the film Money Panai = Maha (l) r. This study aims to determine the meaning of denotation, connotation and myths in the film Money Panai = Maha (l) r, knowing Bugis-Makassar Cultural Representation shown in Money Money Panai = Maha (l) r. This research uses qualitative research type with semiolysis analsis approach Roland Barthes. Subjects in this study are Scene-Scene in the Money Money Movement = Maha (l) r Makkita Cinema Production production in collaboration with 786 Productions. This study uses data collection techniques through documentation and literature study. To achieve the validity of data in this study, the authors use triangulation techniques. The results show that there are three corresponding meanings in Roland Barthes's semiotics. The meaning of denotation contained in the scene of the Money Panai film = = Maha (l) r describes the character of the bugis-makassar community as the Perantau, Asking for Opinion and Restu, Penjajakan, Kinship, Proposal, and Self-Esteem. Meaning of connotation gained in this film in the form of action figures, meaning of utterance based on implicit meaning in dialogue that presented depict value, custom, kinship and moral message. The meaning of myth / ideology contained in several scenes is interpreted through literature review on the culture of bugis-makassar that understand the values of customs, and culture of Self-esteem or siri 'which has been inherited and entrenched among the people of bugis-makassar. Keyword : Representation, Film, Semiotic, Culture, Bugis-Makassar